Biochemical characterization of an inverting S/O-HexNAc-transferase and evidence of S-linked glycosylation in Actinobacteria. (18th August 2021) - Sharma, Yogita; Ahlawat, Shimona; Rao, Alka
Abstract: Antimicrobial peptides harboring S- and or O-linked glycans are known as glycocins. Glycocins were first discovered and best characterized in Firmicutes. S-glycosylation is an enzymatic process catalyzed by S-glycosyltransferases of the GT2 family. Using a heterologous expression system, here we describe an inverting S/O-HexNAc-transferase (SvGT), encoded by ORF AQF52_3101 of Streptomyces venezuelae ATCC 15439, along with its acceptor substrate (SvC), encoded by ORF AQF52_3099 . Using in vitro and in vivo assays, we define the distinct donor specificity, acceptor specificity, regioselectivity, chemoselectivity and Y(G/A/K/Q/E ≠ ΔG)(C/S/T ≠ Y/N)(G/A ≠ P/Q)G as the minimum acceptor sequon of SvGT. Although UDP-GlcNAc served as the donor in the cellular milieu, SvGT could also utilize UDP-Glc and UDP-GalNAc as donors in vitro. Using mass spectrometry and western blotting, we provide evidence that an anti-O-GlcNAc antibody (CTD110.6) cross-reacts with S-GlcNAc and may be used to detect S-GlcNAcylated glycoconjugates directly. With an understanding of enzyme specificities, we finally employed SvGT to generate two proof-of-concept neoglycocins against Listeria monocytogenes . In conclusion, this study provides the first experimental evidence for S-glycosylation in Actinobacteria and the application of its S/O-HexNAc-transferase in glycocin engineering.